Marching in Parallel with the Times - Capulong, Regina (Philippine Journal of Allergy, Asthma and Immunology, 2022)
The Philippine Society of Allergy, Asthma, and Immunology (PSAAI) has come a long way since its founding 50 years ago with 11 allergists. Through the years, the Society has been able to keep up with the various changes in health and medical research and technological developments. It is with this that we would like to introduce the Philippine Journal of Allergy, Asthma, and Immunology’s 1st online edition. With these developments, PSAAI has continued to stay loyal to its aims. In promoting awareness, prevention, and management of allergic and immunologic diseases, this issue consists of studies regarding atopic dermatitis, asthma, and reproductive immunology. To uphold excellent standards in training and teaching, PSAAI has regularly held scientific meetings in discussing cases managed by our fellows-in-training and consultants. One of which is a case report on Behçet’s disease, which is included in this issue. In light of the current COVID-19 pandemic, PSAAI has been at the forefront of initiating and formulating position statements and doing reviews on COVID-19 management, vaccination, and adverse events following immunization. One of these reviews done by PSAAI on COVID-19 vaccination (An interim review of the efficacy and safety of the second COVID-19 booster dose for young, healthy, immunocompetent adults aged 60 and below) is found in this issue. This issue is only the beginning of our journey as a peer-reviewed online journal. Learning does not stop here as we continue to fulfill the Society’s aims in response to the changing times. Learning is a process that invites collaboration with others. With that, we are looking forward to publishing studies that extend beyond PSAAI’s membership. We hope to contribute to the continuous developments in allergy and immunology in pursuit of new scientific knowledge.